(untitled) (The Pakistan Development Review, 2005)
Trade is presumed to act as a catalyst of economic growth and the growth in exports leads to increase in the incomes of factors of production, which in turn increases the demand for input for further expansion in production. The resultant pressure on domestic capacity may stimulate technological change and investment opportunities. Also increase in demand due to raising incomes of the factors of production on account of exports may spill over into other sectors of the economy. A part of such growths could also be diffused abroad through technical assistance and aid. According to Emery (1967) empirically proved that higher rates of exports growth leads to higher economic growth. Traditionally, a developing country had the choice of two alternative trade strategies for supporting industrial development, export promotion or import substitution. A consensus has emerged among many development economists that an export expansion policy by permitting resource exploitation according to comparative advantage and by allowing for utilisation and exploitation of economies of scale leads to higher growth rates of output and employment, greater technological progress and availability of foreign exchange. These in turn enable the countries with export oriented policies to attain higher rates of growth of GNP vis-à-vis countries following import substituting industrialisation [Donges and Muller-Ohlsen (1978)].